Parameter calibration of American ginseng seeds for discrete element simulation - Zhang, Wenxin; Wang, Fangyan (International Journal of Agricultural and Biological Engineering, 2022)
The accurate contact parameters of American ginseng seed particles,which are the basis for establish the discrete element simulation model of American ginseng seeds.The parameters of American ginseng seeds were calibrated by combining the physical tests and simulation tests together. The basic physical parameters, contact parameters and repose angle of sprouted American ginseng seeds were determined by physical tests. The simulation parameters were significantly screened by conducting the Plackett-Burman test. Meanwhile, it was determined that the collision recovery coefficient, static friction coefficient and rolling friction coefficient of interspecific contact parameters have significant influences on the repose angle of the simulation test. By the steepest climb test, the optimal interval for the value of the significance parameter was determined. Subsequently, the second-order regression equation between contact parameters and the repose angle was established, the regression equation was optimized and solved, and the best combination of simulation parameters was determined. The collision recovery coefficient between sprouted American ginseng seeds was 0.346, the static friction coefficient was 0.769, and the rolling friction coefficient was 0.490. By the calibrated seed group of American ginseng for discrete element simulation test, the average repose value angle was 38.80°, and the relative error with the measured repose angle was 0.733%. The results revealed that the simulation parameters of American ginseng seeds were reliable, which can provide a basis for the design and performance optimization of American ginseng seed-metering device in the later stage. Keywords: American ginseng seed, parameter calibration, discrete element, experiments DOI: 10.25165/j.ijabe.20221506.7338 Citation: Zhang W X, Wang F Y. Parameter calibration of American ginseng seeds for discrete element simulation. Int J Agric & Biol Eng, 2022; 15(6): 16–22.